P3-S4.04 Topical 80% Trichloroacetic Acid (TCA) shows efficacy in the treatment of internal High-Grade Anal Intraepithelial Neoplasia (HGAIN). (10th July 2011) - Ho, K; Elishaev, E; Maciak, D; Baker, J; Parzynski, C; Zhu, C; Day, R; Cranston, R
Abstract : Background: HIV positive men who have sex with men (MSM) are at 60–70 times increased risk of developing anal squamous cell carcinoma than the general population. HGAIN, the putative precursor to cancer, may be ablated by various methods in order to prevent neoplastic progression. While TCA has previously been used clinically to treat keratinised external anal warts, it may also be used to ablate internal HGAIN. Here we report on treatment efficacy and clinical predictors of success. Methods: A retrospective chart review of all patients seen at the Anal Dysplasia Clinic at the Pittsburgh AIDS Center for Treatment was performed between 1 January 2008 and 30 June 2010. 41 HIV positive MSM had biopsy proven HGAIN (AIN1/2, AIN2, AIN 2/3, and AIN3) at high-resolution anoscopy. Treatment involved applying three sequential cotton swabs soaked in 80% TCA to the lesion. Patients were seen at an average of 6 months following treatment for follow-up. Clearance was defined as the absence of HGAIN epithelial markers at HRA (punctuation/mosaicism) or AIN 1/normal epithelium on biopsy. The impact of the following variables on lesion clearance were assessed using univariate logistic regression analysis: age, CD4 count, initial grade of dysplasia on biopsy, concomitant therapy with imiquimod, previous history of HGAIN treatment. Results: The mean age of the study population was 52 years and the mean CD4 count was 565 cells/ml. Of the 43 HGAIN lesions treated in 41 patients, 22 (51%) demonstrated clearance of HGAIN epithelial markers. Repeat biopsy was performed on eight lesions and 4 (9%) lesions were AIN1, 3 (7%) lesions were AIN2, and one lesion was ungradable. By univariate logistic regression analysis, patients with a diagnosis of AIN1/2 (compared with those who had AIN2 or greater) demonstrated a non significant trend towards clearance of abnormal visual markers (OR 3.8 p=0.112). All other predictive variables did not achieve statistical significance. Conclusions: On a per lesion basis, the success of a single visit triple topical application of TCA was 58% that is comparable with previously published treatment studies using techniques such as infrared coagulation. While larger prospective studies are called for, following exclusion of cancer by biopsy, HRA combined with TCA treatment may represent a low-cost, minimally invasive management strategy for this population with a high-incidence of HGAIN.